2021
DOI: 10.1029/2021wr030581
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Core Floods in Heterogeneous Sandstone and Carbonate Rocks

Abstract: Integrating numerical modelling and experimental observations is essential to characterising small-scale heterogeneity for subsurface flow • Capillary heterogeneity characterisation in carbonates was only successful when 10 key features were resolved in X-ray imagery 11 • Isotropic capillary heterogeneity in carbonates results in a non-monotonic rate-12 dependant relative permeability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 57 publications
(109 reference statements)
0
20
0
Order By: Relevance
“…They were derived from two sandstone and three carbonate rock cores representing a range of heterogeneous properties. The data sets comprise observations from steady state core-flooding experiments that were previously performed and reported (Manoorkar et al, 2021;Reynolds & Krevor, 2015;Reynolds et al, 2018;Wenck et al, 2021). The experiments co-injected nitrogen and water or supercritical CO 2 and brine at high (HR) and low (LR) flow rates to obtain flow parameters in the viscous-limit (VL) and capillary-limit (CL) flow regimes, with capillary number in Table S6 of Wenck et al (2021).…”
Section: Experimental Data Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were derived from two sandstone and three carbonate rock cores representing a range of heterogeneous properties. The data sets comprise observations from steady state core-flooding experiments that were previously performed and reported (Manoorkar et al, 2021;Reynolds & Krevor, 2015;Reynolds et al, 2018;Wenck et al, 2021). The experiments co-injected nitrogen and water or supercritical CO 2 and brine at high (HR) and low (LR) flow rates to obtain flow parameters in the viscous-limit (VL) and capillary-limit (CL) flow regimes, with capillary number in Table S6 of Wenck et al (2021).…”
Section: Experimental Data Setsmentioning
confidence: 99%
“…The element volume must be large enough such that the definition of a continuum property such as permeability is valid, while sufficiently small so that heterogeneities in these properties are captured (see Jackson et al (2018)). The size of the element volume for this work was chosen to be 2 mm (Manoorkar et al, 2021;Wenck et al, 2021). The initial setup, depicted in Algorithm 1 and Figure A1 of the Appendix A, is followed by the image processing and upscaling of experimental parameters.…”
Section: Model Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the DRP technique can be employed to simulate multiphase flow in core samples (Ruspini et al., 2021; S. Wang et al., 2022). Tuning the numerical modeling of multiphase flow in porous media with sub‐core‐scale heterogeneity, obtained by DRP analysis, to generate results consistent with experimental observations have always been met as a serious and considerably difficult challenge (Wenck et al., 2021). Typically, it has been observed that the estimation of sub‐core‐scale permeability based on porosity distribution leads to the saturation distributions not matching with experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2022). Tuning the numerical modeling of multiphase flow in porous media with sub-core-scale heterogeneity, obtained by DRP analysis, to generate results consistent with experimental observations have always been met as a serious and considerably difficult challenge (Wenck et al, 2021). Typically, it has EBADI ET AL.…”
mentioning
confidence: 99%